2020
DOI: 10.1002/fut.22113
|View full text |Cite
|
Sign up to set email alerts
|

The theory of storage in the crude oil futures market, the role of financial conditions

Abstract: This study examines the impacts of inventory and financial instability on the basis of the crude oil market. The results show that, first, the basis rises with inventory, and this effect is higher during low inventory regimes. This validates the theory of storage in the crude oil market. Second, the basis rises with financial instability, and this effect is higher during turbulent regimes. These results warn the oil market participants that, to make decisions based on the basis variation, traditionally known a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The similarity of the crude oil importers between China and Japan, and the sensitivity of EPU Japan to the global oil demand shock might contribute to the superior predictive power of EPU Japan compared with other countries. Third, compared with other countries, previous literature shows the EPU from Japan and United Kingdom are closely related to Chinese economic conditions such as the financial conditions (Liu Z. et al, 2019;Li and Zhong., 2020;Ahmadi et al, 2020), monetary aggregate (Han et al, 2016), exchange rate (Chen et al, 2020;Zheng and Kaizoji, 2019), and market uncertainty Smales, 2020). These factors are closely related to the crude oil market (Ahmadi et al, 2020;Yousefi and Wirjanto, 2004;Ratti and Vespignani, 2013), thus it is reasonable that the EPUs from these two counties may contain information of the future volatility of the INE crude oil futures market.…”
Section: Out-of-sample Evaluationmentioning
confidence: 99%
“…The similarity of the crude oil importers between China and Japan, and the sensitivity of EPU Japan to the global oil demand shock might contribute to the superior predictive power of EPU Japan compared with other countries. Third, compared with other countries, previous literature shows the EPU from Japan and United Kingdom are closely related to Chinese economic conditions such as the financial conditions (Liu Z. et al, 2019;Li and Zhong., 2020;Ahmadi et al, 2020), monetary aggregate (Han et al, 2016), exchange rate (Chen et al, 2020;Zheng and Kaizoji, 2019), and market uncertainty Smales, 2020). These factors are closely related to the crude oil market (Ahmadi et al, 2020;Yousefi and Wirjanto, 2004;Ratti and Vespignani, 2013), thus it is reasonable that the EPUs from these two counties may contain information of the future volatility of the INE crude oil futures market.…”
Section: Out-of-sample Evaluationmentioning
confidence: 99%
“…F is the time t settlement price of a contract that matures at time T. The use of absolute prices in the return definition is dictated by the negative price observed on April 3. Geman and Ohana (2009), Symeonidis et al (2012), Geman and Smith (2013), Gorton et al (2013), Alquist et al (2020), andAhmadi et al (2020) confirmed empirically for different commodity markets that low (high) inventory levels are associated with forward curves in backwardation (contango). Using intraday data, Alquist et al (2020) showed that news of higher-than-expected (lower-than-expected) U.S. crude oil inventories lead to very quick decreases (increases) in the front futures contract price, even within minutes of the announcement.…”
Section: Futures Pricesmentioning
confidence: 61%
“…Our results are in line with the results of Fama and French (1988) 1 , Kucher and Kurov (2014) 2 , and Serletis and Shahmoradi (2006), where the standard deviation of the negative IABs is higher when compared to the standard deviation of the positive IABs. Some studies (Ahmadi et al, 2020;Fama & French, 1988;Kucher & Kurov, 2014;Stronzik et al, 2008) though did not conform to the theory, as the standard deviation of positive IABs are found to be higher in comparison to the standard deviation of the negative IABs. 2.…”
Section: Resultsmentioning
confidence: 89%
“…Two important methods to test the theory of storage are found in the literature: the direct method (Anand, 1999;Brennan, 1958;Cho & McDougall, 1990;Geman & Nguyen, 2005;Geman & Smith, 2013;Gray & Peck, 1981;Heaney, 1998;Kucher & Kurov, 2014;Lien, 1987;Omura et al, 2015;Telser, 1958;Thompson, 1986;Working, 1949) and the indirect method (Ahmadi et al, 2020;Brooks et al, 2013;Fama & French, 1987, 1988Serletis & Hulleman, 1994;Serletis & Shahmoradi, 2006;Stronzik et al, 2008). In the direct testing method, convenience yield is calculated by the spot and futures prices and modelled with the real inventory data of the commodity.…”
Section: Literature Reviewmentioning
confidence: 99%